Estrategias de publicidad en la Cafetería Cafecito de la ciudad de Babahoyo en el periodo 2022 - Flores Monserrate, Santiago Miguel (2023)
The case study which is titled: advertising strategies in the café cafecito in the city of Babahoyo in the period 2022, has as its main objective Evaluate the advertising strategies that the establishment maintains and identify the shortcomings that it maintains due to little innovation. Within its processes and the implementation in new advertising models, to carry out this study, some techniques were carried out, such as the survey applied to customers in order to know the opinion of each one regarding the establishment and the customer service processes. clients, in addition to knowing how pleasant the advertising is, an interview was also carried out, this was addressed to the owner, it was carried out to know the knowledge she has about the subject raised, all this information that was collected was of vital importance to make the recommendations about an improvement in the positioning and the acquisition of new clients for the increase of their sales.